Enhancing Community Participation in Regional Development Planning Through a Bottom-Up Approach - Syafaruddin; Abdul Haris (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This study examines strategies for enhancing community participation in regional development planning by implementing bottom-up approaches. As democratic governance evolves, the need for meaningful citizen engagement in development planning becomes increasingly critical for ensuring sustainable and equitable outcomes. This research analyzes the effectiveness of participatory planning mechanisms, identifies barriers to community engagement, and proposes innovative strategies for strengthening bottom-up development planning processes. Using a comparative case study methodology across six regional governments, this study evaluates various participatory instruments including citizen forums, participatory budgeting, community mapping, and digital engagement platforms. The findings reveal that successful bottom-up planning requires institutional commitment, capacity building, cultural sensitivity, and sustained dialogue between government and communities. The study provides a framework for designing and implementing effective participatory planning systems that genuinely incorporate community voices in regional development decisions.